2021
DOI: 10.1186/s13023-021-01798-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic characteristics of hypophosphatasia in Chinese children

Abstract: Background Hypophosphatasia (HPP) is a rare inherited disorder, which is caused by loss-of-function mutations in the ALPL gene. HPP is a heterogeneous disease that has a wide spectrum of phenotypes. Few studies were carried out in the Chinese population with HPP, especially in children. Methods The clinical and genetic characteristics of 10 Chinese children with HPP who were referred to the Beijing Children’s Hospital were described. Previously rep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
1
3
0
1
Order By: Relevance
“…In the current study, c.407G>A (p.Arg136His) and c.984_ 986delCTT (p.Phe328del) were found in three and two unrelated patients, respectively, indicating the high prevalence of HPP in Chinese adults. c.407G>A (p.Arg136His) was also reported in other Chinese HPP cohorts [ 27 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the current study, c.407G>A (p.Arg136His) and c.984_ 986delCTT (p.Phe328del) were found in three and two unrelated patients, respectively, indicating the high prevalence of HPP in Chinese adults. c.407G>A (p.Arg136His) was also reported in other Chinese HPP cohorts [ 27 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 70%
“…Zhang, et al [ 28 ] reported the clinical and genetic results of pediatric-onset HPP patients from five unrelated families and investigated the pathogenicity of mutations with in-depth bioinformatic analysis. Liu, et al [ 29 ] reported the clinical, laboratory, and genetic findings of 33 pediatric-onset HPP patients and explored the differences between perinatal, infantile, childhood, and odonto subtypes. However, the characteristics and current situation of adult HPP in the Chinese population remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the frequency of the c.787T > C/p.Tyr263His variant in the Japanese population is 0.31–0.55, and in the gnomAD database, 0.1833 [ 28 , 29 ] of the p.Asp378Val and p.Leu520ArgfsX86 variants are most common in the USA [ 6 ] and Japan [ 30 ], respectively. The majority of the mutations in the ALPL gene were localized in the 5th, 7th, 10th, and 3rd exons [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…By February 2022, more than 500 pathogenic variants of the ALPL gene were registered in the Global Variome Shared International Database [ 17 ]. Among all ALPL genetic variants, missense mutations account for 71.2%, deletions 11.0%, splice mutations 4.9%, nonsense mutations 4.6%, insertions 3.4%, large deletions/duplications 2.9%, insertions/deletions 1.5%, and regulatory mutations 0.2% [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ген ALPL картирован на коротком плече 1-й хромосомы -1p36.12 -и состоит из 12 экзонов. В настоящее время описано более 410 различных мутаций в гене ALPL [1].…”
unclassified